Quantitative prediction of charge regulation in oligopeptides. Issue 2 (8th December 2020) - Lunkad, Raju; Murmiliuk, Anastasiia; Hebbeker, Pascal; Boublík, Milan; Tošner, Zdeněk; Štěpánek, Miroslav; Košovan, Peter
Abstract : Charge regulation in the peptide Glu5 –His5 as a model weak ampholyte: simulations predict deviations from the ideal ionization of free aminoacids, in quantitative agreement with experiments. Abstract : Weak ampholytes are ubiquitous in nature and commonly found in artificial pH-responsive systems. However, our limited understanding of their charge regulation and the lack of predictive capabilities hinder the bottom-up design of such systems. Here, we used a coarse-grained model of a flexible polymer with weakly ionisable monomer units to quantitatively analyse the ionisation behaviour of two oligopeptides as model ampholytes. Our simulations predict differences in the charge states between oligopeptides and monomeric amino acids, showing that not only electrostatic interactions between charged groups but also conformational flexibility plays a key role in the charge regulation. By comparing our simulations with experimental results from potentiometric titration, capillary zone electrophoresis and NMR, we demonstrated that our model reliably predicts the charge state of various peptide sequences. Ultimately, our simulation model is the first step towards understanding the charge regulation in flexible ampholytes, and towards predictive bottom-up design of charge-regulating systems.